2016
DOI: 10.5430/jnep.v6n11p97
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating design and transforming baccalaureate nursing education to foster a culture of health

Abstract: Healthcare reform and changing population health demographics call for a radical transformation in healthcare delivery and the education of healthcare providers. Nurses comprise the largest proportion of healthcare providers making it necessary to ensure that they are prepared to address the challenges that arise from the evolving healthcare delivery system. A key message of The Institute of Medicine's The Future of Nursing: Leading Change, Advancing Health, is that nurses must lead healthcare change. To accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The CNs drafted syllabi including course title, course objectives, content outlines, and proposed evaluation methods that reflected curricular themes, end of program outcomes, level competencies, and most importantly the plan of study needed to realize the vision of the College -educating professional registered nurses who will form and lead the integrated healthcare delivery and research teams for the 21 st century -a change agent capable of fostering a new culture of health. [6] The plan of study addressed the ideal foundational skill set so that graduates would be prepared to provide care across transitions; care for people along the healthcare continuum in settings such as primary care, ambulatory care, home, community; and other "outside the box" settings such as shelters, churches, and libraries to name a few. Experiential learning and service learning opportunities were included in the new curriculum, and clinical rotations were renamed as immersion experiences.…”
Section: Individual Course Syllabi: Planning and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNs drafted syllabi including course title, course objectives, content outlines, and proposed evaluation methods that reflected curricular themes, end of program outcomes, level competencies, and most importantly the plan of study needed to realize the vision of the College -educating professional registered nurses who will form and lead the integrated healthcare delivery and research teams for the 21 st century -a change agent capable of fostering a new culture of health. [6] The plan of study addressed the ideal foundational skill set so that graduates would be prepared to provide care across transitions; care for people along the healthcare continuum in settings such as primary care, ambulatory care, home, community; and other "outside the box" settings such as shelters, churches, and libraries to name a few. Experiential learning and service learning opportunities were included in the new curriculum, and clinical rotations were renamed as immersion experiences.…”
Section: Individual Course Syllabi: Planning and Sequencingmentioning
confidence: 99%
“…Considering these three continuums, as well as the ideas gleaned from faculty, students, alumni, practice partners, and environmental scans of existing literature, working papers, government, regulatory, and advisory body reports, four themes emerged: 1) population health, 2) interprofessional collaboration, 3) innovation, and 4) practice excellence. [6] 3.1 End of program outcomes and level competencies The end of program outcomes were formed by all the information and data collected from stakeholders, as well as the tables of evidence. Synthesis of all the collected information and data revealed that the ideal graduate would have the knowledge, skills, competencies, and attitudes necessary to practice in any care setting they found themselves in as new graduate nurses (acute care, ambulatory care, or transitional setting).…”
Section: Curriculum Designmentioning
confidence: 99%
“…Despite the growing demands on primary care and the value of primary care nurses, an integrative review showed that nursing curricula in Australia, United Kingdom, United States, New Zealand, and Canada tend to be acute care-focused depicting negative perceptions of the primary care nursing role, which has impacted undergraduate students’ attitudes and preparedness to work in this setting ( Calma et al., 2019 ). Given the changing roles of nursing in health-care delivery, the focus on health over disease-based and acute care-focused curricula, and the need to increase knowledge and skills in care coordination and interprofessional team-based care ( Bouchaud et al., 2016 ), baccalaureate nursing programs need to elevate primary care content in programs and prepare students for roles in primary care ( Barton, 2017 ; Calma et al., 2019 ; Shaffer et al., 2018 ). Therefore, the goal of this article is to explore third-year Canadian baccalaureate nursing students’ perceptions of an innovative primary care clinical placement aimed at serving community-dwelling older adults.…”
mentioning
confidence: 99%
“…The second part discusses how undertaking these activities then came to influence the adoption of Complexity Thinking [1] in the design of our conceptual model, which then guided our program structure and learning and teaching approaches. We share these experiences to illustrate the steps we undertook on this journey, to outline and example the program we created, and to continue the scholarly discussions around design of baccalaureate nursing program structures, [2,3] especially those associated pedagogies inspired by the concepts related to Complexity Theory. [4] Although couched within an Australian setting we believe there will be many commonalties with nursing education providers in other countries where faculties are seeking to renew their curricula to meet healthcare needs in what has become a very complex and challenging world in which to provide nursing care.…”
Section: Introductionmentioning
confidence: 99%